The Family Support and Knowledge of Childbearing Age Women Intention to Prevent Cervical Cancer by Using Visual Inspection with Acetic Acid (VIA) Examination - Supatmi, Supatmi; Susanti, Ade; Wahyuni, Dinda Tri; Yunitasari, Esty (International Journal of Psychosocial Rehabilitation, 2020)
Cervical cancer is second cancer for women in the world especially in development countries. Examining visual inspection with Acetic Acid (VIA) is one of the ways to detect early the cervical cancer easily and simply, but actually there are still many women of childbearing age who don’t want to do it because the family support and knowledge are still low. This study aims to determine the relationship between the family support and knowledge with intention women of childbearing age to VIA. The research method was correlation analytical by used sectional cross. The population was 72 respondents and the sampling 61 respondents which used simple random sampling. The independent variable was the family support and knowledge and the dependent variable was women of childbearing age. The instrument used was questionnaire. The data analysis used was Spearman Rank Test p < 0,05. There was relation between family support and intention women of childbearing age to examine visual inspection with acetic acid (VIA) ( p = 0,000; r=0482 ), and there was relation between knowledge and intention women of childbearing age to VIA (p = 0,003; r=0,376). The family support and knowledge related intention women of childbearing age to examine visual inspection with acetic acid (VIA). The specific knowledge about cancer screening cervical cancer and the family support was important element in order to determine what woman would examine visual inspection by used acetic acid (VIA).